Legal pragmatics - Kurzon, Dennis; Kryk-Kastovsky, Barbara (Pragmatics & beyond, 2018)
"The volume Legal Pragmatics is a contribution to the interface between language and law. It looks at how the principles of language use can be beneficial to clarifying legal issues, its twelve chapters (together with the Introduction) offering a wide spectrum of the latest approaches to the area of legal pragmatics. The four chapters in the first section are devoted to historical pragmatics and take a diachronic look at old courtroom records. Written legal language is also the focus of the four chapters in the next section, dealing with the pragmatics of modern legal writing. The chapters in the third section, devoted to modern legal language, touch upon both the discourse in the courtroom and in police investigation. Finally, the two chapters in the last section on legal discourse and multilingualism address a topic very relevant to the modern era of globalisation -- the position of legal discourse in multilingual contexts."--